Patanjali: The Story of a Yoga Brand - Chakraborty, Ishani (Ushus Journal of Business Management, 2021)
"Look at how the company has grown. ITC’s FMCG business is around Rs 5,000 crore. Patanjali has disrupted the FMCG space with simple products that promise the goodness of tradition"1.Arvind Singhal, retail expert and founder of Technopak"He has got his branding spot on. He has gone back to the basics. His ads are rustic, he talks about the products. I’m excited about Ramdev. He could turn out to be the silent MNC killer of the future"2.Harish Bijoor, Brand Expert